Helicobacter pylori, gastritis, and peptic ulceration in the elderly. Issue 12 (December 1992) - Wyatt, J I; Shallcross, T M; Crabtree, J E; Heatley, R V
Abstract : AIMS: To determine the histopathological types of gastritis, presence of H pylori, and of peptic ulceration in patients aged 70 and over, compared with younger adults. METHODS: Gastric antral and corpus biopsy specimens from 112 elderly patients were classified and graded histologically according to the Sydney system. Details of recent antibiotic and non-steroidal anti-inflammatory drug use were recorded. Eighty four of the patients were positive for H pylori IgG antibodies and parietal cell antibodies. The results were compared with those from a series of 124 adult patients aged under 60. RESULTS: H pylori were visible at histological examination in only 57 of 87 (65.5%) elderly patients with chronic gastritis (excluding "special forms") compared with 72 of 79 (91.1%) of the younger patients with gastritis (p < 0.0002). Severe atrophy of the corpus mucosa was significantly associated with absence of H pylori (p < 0.002), and was present in eight of 30 elderly patients with helicobacter negative gastritis. Other explanations for absence of H pylori include recent antibiotic intake, more intestinal metaplasia, and lower bacterial load in elderly patients (p < 0.05). Autoimmune gastritis and NSAID use did not seem to be relevant. Serodiagnosis showed reduced sensitivity (81%) in patients who were helicobacter positive histologically, but was positive in 14 of 23 (61%) with H pylori negative gastritis histologically, suggesting either current infection that had been missed or previous infection. Peptic ulceration was significantly associated with NSAID use, but not with H pylori in the elderly. CONCLUSIONS: The spectrum of gastritis is different in the elderly, compared with younger adults, due to a significant group with chronic gastritis who are H pylori negative on histological examination. NSAID use, but not demonstration of H pylori (at histological examination) is associated with peptic ulceration in the elderly.